2005
DOI: 10.1007/s10488-005-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Voices: Consumers with Serious Mental Illness Speak About Intensive Case Management

Abstract: This study explores early alliance formation between adult consumers with schizophrenic-spectrum disorders and their case managers from the consumers' perspectives using a prospective, cohort design. While quantitative studies have demonstrated positive links between the alliance and some client outcomes, such methods cannot reveal in concrete and authentic ways what consumers want in the case management relationship. This study finds that consumers can provide tangible and insightful information about the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…Furthermore, for professionals to be physically available, to be accessible and acknowledge requests when they occur [23, 24, 27, 29, 31-34, 37, 38, 41] and be able to help when challenges arise [22,23,27,30,31,36,39,41] is described as helpful. In addition, what can be called affective availability is described in the studies.…”
Section: Time and Availabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, for professionals to be physically available, to be accessible and acknowledge requests when they occur [23, 24, 27, 29, 31-34, 37, 38, 41] and be able to help when challenges arise [22,23,27,30,31,36,39,41] is described as helpful. In addition, what can be called affective availability is described in the studies.…”
Section: Time and Availabilitymentioning
confidence: 99%
“…In addition, what can be called affective availability is described in the studies. This pertains to the fact that a professional is available for the individual because s/he cares about them, being there as a person for them [23,26,27,30,31,41]. ''She was there for me, not for her job or the system, but because she wanted to be'' [23, p. 476].…”
Section: Time and Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative studies have provided insight into what consumers find valuable in their relationships with providers; looking for common ground, feeling known, the importance of talk, and feeling like ''somebody'' (Ware et al 2004). Buck and Alexander (2005) applied this ''model of connectedness'' to case management relationships and found that consumers saw their case managers as an important conduit into the social world. In fact, the extent to which consumers articulated a desire for friendship with providers often challenges professional practice norms of maintaining clinical boundaries.…”
Section: Relationships In Actmentioning
confidence: 99%